TINJAUAN YURIDIS PERLINDUNGAN HUKUM TERHADAP PELAPOR TINDAK PIDANA KORUPSI BERDASARKAN PERATURAN PEMERINTAH NOMOR 43 TAHUN 2018 TENTANG TATA CARA PELAKSANAAN PERAN SERTA MASYARAKAT DAN PEMBERIAN PENGHARGAAN DALAM PENCEGAHAN DAN PEMBERANTASAN TINDAK PIDANA KORUPSI - Tio Jatmika; Mexsasai Indra; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Corruption is a violation of social rights and economic rights of the community, so that criminal acts of corruption can no longer be classified as ordinary crimes but have become extraordinary crimes. Protection for reporters related to corruption is regulated in Government Regulation No. 43 of 2018 concerning Procedures for the Implementation of Community Participation and the Appreciation of the Prevention and Eradication of Corruption. Therefore, the formulation of the problem of this thesis writing is: First, how is the legal protection for the reporters of criminal acts of corruption based on Government Regulation Number 43 of 2018 concerning Procedures for the Implementation of Community Participation and Awarding in Prevention and Eradication of Corruption Crimes? Secondly, is legal protection given to Reporters whose reports do not contain the truth?.This type of research used by the author is normative legal research, also called doctrinal legal research. In this normative legal research, the author is interested in conducting research using the systematic criteria of law. Sources of data used, namely: primary data, secondary data and tertiary data. Data collection techniques in this study using the method of literature study that is the researcher analyzes based on books, legislation and other literature related to the problem under study. Data analysis was carried out qualitatively ie the data obtained were not using statistics or mathematics or the like. In drawing conclusions the author uses the method of deductive thinking that is a way of thinking that draws conclusions from a statement or general proposition into a statement or case that is specific.Conclusions from the results of the study, first, the rules regarding protection for reporters are not maximally provided such as protection for witnesses and victims. Article 2 of the Republic of Indonesia Law No. 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection of Witnesses and Victims provides protection for witnesses and victims at all stages of criminal justice in a court of law. Whereas the reporter who is also a witness did not receive an award for the report he reported and there was no legal certainty. Second, the reporter whose report does not contain the truth means that there is no legal protection. It should be that the Reporting Party whose report contains the truth or whose report does not contain the truth must still be given legal protection.Keywords: Corruption - Reporting - Legal Protection